Structural and emission properties of Eu3+‐doped alkaline earth zinc‐phosphate glasses for white LED applications. Issue 4 (2nd February 2017) - Jha, Kaushal; Jayasimhadri, Mula
Abstract: Quaternary alkaline earth zinc‐phosphate glasses in molar composition (40 − x )ZnO – 35P2 O5 – 20RO – 5TiO2 – x Eu2 O3 (where x =1 and R=Mg, Ca, Sr, and Ba) were prepared by melt quenching technique. These glasses were studied with respect to their thermal, structural, and photoluminescent properties. The maximum value of the glass transition temperature ( T g ) was observed for BaO network modifier mixed glass and minimum was observed for MgO network modifier glass. All the glasses were found to be amorphous in nature. The FT‐IR suggested the glasses to be in pyrophosphate structure, which matches with the theoretical estimation of O/P atomic ratio and the maximum depolymerization was observed for glass mixed with BaO network modifier. The intense emission peak was observed at 613 nm ( 5 D0 → 7 F2 ) under excitation of 392 nm, which matches well with excitation of commercial n ‐UV LED chips. The highest emission intensity and quantum efficiency was observed for the glass mixed with BaO network modifier. Based on these results, another set of glass samples was prepared with molar composition (40 − x )ZnO – 35P2 O5 – 20BaO – 5TiO2 – x Eu2 O3 ( x =3, 5, 7, and 9) to investigate the optimized emission intensity in these glasses. The glasses exhibited crystalline features along with amorphous nature and a drastic variation in asymmetric ratio at higher concentration (7 and 9 mol%) of Eu2 O3 . The color of emission also shifted from red to reddish orange with increase in the concentration of Eu2 O3 . These glasses are potential candidates to use as a red photoluminsecent component in the field of solid‐state lighting devices.